2004
DOI: 10.1158/0008-5472.can-04-0715
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Regulates Aberrant Expression of Insulin-Like Growth Factor-Binding Protein 3

Abstract: Epidermal growth factor receptor (EGFR) is frequently overexpressed in esophageal carcinoma and its precursor lesions. To gain insights into how EGFR overexpression affects cellular functions in primary human esophageal cells, we performed gene expression profiling and identified insulin-like growth factor-binding protein (IGFBP)-3 as the most upregulated gene. IGFBP-3 regulates cell proliferation through both insulinlike growth factor-dependent and independent mechanisms. We found that IGFBP-3 mRNA and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 55 publications
8
85
0
Order By: Relevance
“…miR-17-5p was markedly downregulated ( Figure 1A) while IGFBP-3 was significantly upregulated ( Figure 1B) in the nonmetastatic liver tissues of HCC patients compared to healthy controls. This goes in line with previous studies showing IGFBP-3 to be highly expressed in breast and esophageal cancer [21,22] . But on the other hand, it contradicts other studies that reported reduced IGFBP-3 mRNA expression and protein levels in metastatic HCC patients [12,13] .…”
Section: Discussionsupporting
confidence: 93%
“…miR-17-5p was markedly downregulated ( Figure 1A) while IGFBP-3 was significantly upregulated ( Figure 1B) in the nonmetastatic liver tissues of HCC patients compared to healthy controls. This goes in line with previous studies showing IGFBP-3 to be highly expressed in breast and esophageal cancer [21,22] . But on the other hand, it contradicts other studies that reported reduced IGFBP-3 mRNA expression and protein levels in metastatic HCC patients [12,13] .…”
Section: Discussionsupporting
confidence: 93%
“…34 One explanation for the overexpression of IGFBP-3 in malignancies is that IGFBP-3 may inhibit tumor cell proliferation via a negative feedback mechanism. 37,[39][40][41][42] Another possibility is that unknown defects in IGFBP-3 receptor function may lead to IGFBP-3 overexpression in these tumors. 22 Overall, the expression and function of IGFBP-3 may differ according to the type of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR family composes of four members: EGFR (HER-1, erbB-1), HER2 (erbB-2, Neu), HER3 (erbB-3) and HER4 (erbB-4) [4,18], all of which are tyrosine kinase receptors that are activated by ligand-induced homo or hetero dimerization. Overexpression of EGFRs is common in esophageal cancer and has been reported in several cell lines of SCCE, 29-92% of tumor samples of SCCE [19,20] and 80% of patients with adeno and squamous cell carcinoma [21,22]. EGFR upregulation correlates with poor prognosis, low survival rate and minimal response to chemotherapy [20,[23][24][25].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%